2010
DOI: 10.1111/j.1472-4669.2010.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

The methane cycle in ferruginous Lake Matano

Abstract: In Lake Matano, Indonesia, the world's largest known ferruginous basin, more than 50% of authigenic organic matter is degraded through methanogenesis, despite high abundances of Fe (hydr)oxides in the lake sediments. Biogenic CH 4 accumulates to high concentrations (up to 1.4 mmol L ) and SO 4 2) in Lake Matano waters suggests that anaerobic methane oxidation may be coupled to the reduction of Fe (and ⁄ or Mn) (hydr)oxides. Thermodynamic considerations reveal that CH 4 oxidation coupled to Fe(III) or Mn(III ⁄ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
181
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(194 citation statements)
references
References 70 publications
(190 reference statements)
13
181
0
Order By: Relevance
“…Li et al, 2013a), the presence of Fe(II)-bearing minerals in IF (e.g., magnetite, siderite, greenalite -recall section 2.3), and the general lack of microfossils preserved in the Fe-rich layers lacking silicification. Moreover, the reduction of ferric iron may also have been coupled to the anaerobic oxidation of methane , an observation supported by the reaction's likely occurrence in modern marine sediments (Riedinger et al, 2014) and lakes (Crowe et al, 2011), as well as in culture experiments (Ettwig et al, 2016;Bray et al, 2017). …”
Section: Available Reductants and Diagenesis Of Iron Formationsmentioning
confidence: 77%
“…Li et al, 2013a), the presence of Fe(II)-bearing minerals in IF (e.g., magnetite, siderite, greenalite -recall section 2.3), and the general lack of microfossils preserved in the Fe-rich layers lacking silicification. Moreover, the reduction of ferric iron may also have been coupled to the anaerobic oxidation of methane , an observation supported by the reaction's likely occurrence in modern marine sediments (Riedinger et al, 2014) and lakes (Crowe et al, 2011), as well as in culture experiments (Ettwig et al, 2016;Bray et al, 2017). …”
Section: Available Reductants and Diagenesis Of Iron Formationsmentioning
confidence: 77%
“…Although AOM coupled with Fe-and Mn-reduction (FDMO and MDMO, respectively) has been proposed to occur in various freshwater environments (e.g. ferruginous lakes Matano and Kinneret; Crowe et al, 2011;Sivan et al, 2011;a Norði et al, 2013), to our knowledge no direct rate measurements have been reported in the literature. In this study, we investigated biogeochemistry of the water column of Dendre stone pit lake (Belgium), a relatively deep (maximum depth 30 m) but small (0.032 km 2 ) water body in a former limestone quarry, with a focus on quantifying AOM rates and related electron acceptors.…”
Section: Introductionmentioning
confidence: 94%
“…Given the 8:1 stoichiometry of Fe 3+ reduced to methane oxidized [3], their contribution to iron cycling, thereby impacting also the geochemistry of phosphorus and sulfur, may be even more important than their impact on the carbon cycle (11,16,18,20). The enrichment of at least one of the microbial players not only now enables a targeted investigation of iron-dependent methane oxidation in physiological and molecular detail, but may also shed light on the long-standing discussion about Fe 2+ -producing processes on early Earth, when AAA-related organisms may have thrived under the methane-rich atmosphere in the ferruginous Archean oceans (12,18,30).…”
Section: Significancementioning
confidence: 99%